2018
DOI: 10.1091/mbc.e17-06-0410
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin histone modifications and rigidity affect nuclear morphology independent of lamins

Abstract: Chromatin decompaction via increasing euchromatin or decreasing heterochromatin results in a softer nucleus and abnormal nuclear blebbing, independent of lamin perturbations. Conversely, increasing heterochromatin stiffens the nucleus and rescues nuclear morphology in lamin-perturbed cells that present abnormal nuclear morphology.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
400
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(445 citation statements)
references
References 61 publications
37
400
7
1
Order By: Relevance
“…Our results show that the nuclei of Bottom-5 cells deform more than Top-5 cells when embedded in a collagen matrix or even when spontaneously migrating on a 2D surface. Previous research has shown that nucleus stiffness can be altered by increasing or decreasing the overall expression of Lamin A/C or by changing overall levels of heterochromatin (Lammerding et al, 2006, Stephens et al, 2017, Stephens et al, 2018. But, the apparent change in nucleus pliability observed in the current study cannot be explained by changes in overall Lamin A/C content or heterochromatin levels: Lamin A/C and H3K9me3 levels were constant as measured by both immunostaining and western blot.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Our results show that the nuclei of Bottom-5 cells deform more than Top-5 cells when embedded in a collagen matrix or even when spontaneously migrating on a 2D surface. Previous research has shown that nucleus stiffness can be altered by increasing or decreasing the overall expression of Lamin A/C or by changing overall levels of heterochromatin (Lammerding et al, 2006, Stephens et al, 2017, Stephens et al, 2018. But, the apparent change in nucleus pliability observed in the current study cannot be explained by changes in overall Lamin A/C content or heterochromatin levels: Lamin A/C and H3K9me3 levels were constant as measured by both immunostaining and western blot.…”
Section: Discussioncontrasting
confidence: 73%
“…Genes within less-accessible heterochromatin tend to be inactive while those localized to more accessible euchromatin tend to be active or poised for quick transcriptional activation (Gaspar-Maia et al, 2011, van Steensel andBelmont, 2017). Chromatin state has also been shown to influence nuclear physical properties: increased levels of heterochromatin increase nuclear stiffness while increased euchromatin levels decrease stiffness and increase nuclear deformability (Stephens et al, 2017, Stephens et al, 2018. Such global changes in chromatin state can also influence confined migration; for example, increasing euchromatin or decreasing heterochromatin inhibits mouse melanoma cell migration (Gerlitz and Bustin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To test their relative contribution for the nuclear asymmetry, we analyzed Dynein distribution on the NE following depletion of Lamin A by RNAi or 315 after treatment with ICRF-193, a Topoisomerase II (TopoII) inhibitor, or Valproic acid (VPA), a histone deacetylase inhibitor (HDAC). Treatment with either TopoII or HDAC inhibitors should interfere with chromatin structure, decreasing overall nuclear stiffness [35]. Interestingly, inhibition of either TopoII or HDACs induced a loss of Dynein specifically on the NE (Fig.…”
Section: Chromatin Condensation Is Required For Centrosome Positioningmentioning
confidence: 95%
“…Radial displacement maps were produced as the radial shift of each point in the membrane with respect to the reference (median) membrane contour. Nuclear irregularity index was calculated as described previously [35].…”
Section: Quantitative Analysis Of Centrosomes Cell Membrane and Nuclmentioning
confidence: 99%
“…At the cellular level, the accumulation of progerin induces progressive alterations of nuclear shape and cellular senescence 27 . Notably, inhibition of PcG functions can trigger "nuclear blebbing", an alteration of the nuclear shape typically observed in Lamin A deficient cells 28 , suggesting that chromatin architecture and nuclear shape strictly depend on each other. Consistently, LADs organization and PcG-dependent H3K27me3 mark are altered in HGPS 29,30 .…”
mentioning
confidence: 99%